Modulation of amygdalar glutamatergic neurotransmission during ethanol withdrawal induced anxiety-like syndrome via MGluR5-PKC epsilon mediated signalling pathway - A/L Murthy, Jayakumar (2015)
Abstinence from chronic ethanol consumption leads to the manifestation of a variety of symptoms attributed to central nervous system hyperexcitability. Recent studies have demonstrated the importance of metabotropic glutamate receptor 5 (mGluR5) in addictive behaviours. This study investigated the role of amygdalar mGluR5-PKC epsilon mediated signalling pathway in the manifestation of ethanol withdrawal (EW) induced anxiety. Male Wistar rats were fed a Modified Liquid Diet (MLD) containing low fat cow’s milk, sucrose, and maltodextrin with a gradual introduction of 2.4%, 4.8% and 7.2% ethanol for 20 days. Six hours into EW, the rats were intraperitoneally injected with normal saline, MPEP (2.5, 5.0, 10, 20, 30 mg/kg) and ethanol (2.5g/kg, 20% v/v) and were assessed for EW induced anxiety using an automated elevated plus maze (EPM) and an open field (OF). MPEP at 10 mg/kg significantly attenuated EW induced anxiety without any compromising effects on locomotor activities of EW rats. However, low doses of MPEP (2.5, 5 mg/kg) significantly compromised the locomotor activities of EW rats. High doses of MPEP (20 and 30 mg/kg) and acute challenge of ethanol significantly attenuated withdrawal anxiety when tested in the EPM but not OF. Administration of MPEP (2.5-30 mg/kg) has no significant compromising effect on the locomotor activities of ethanol naive rats. Following Western Blot analysis, significant increase in protein levels of mGluR5, total PKC epsilon and phosphorylated PKC epsilon was seen in the amygdala of EW rats. MPEP (10mg/kg) produced significant reduction in the protein levels of phosphorylated PKC epsilon. MPEP (2.5-30mg/kg) had no significant effect on the total protein levels of PKC epsilon and mGluR5. Acute ethanol challenge increased the protein expression of phosphorylated PKC epsilon in the amygdala of EW rats but showed less alterations in the protein levels of total PKC epsilon and mGluR5 compared to EW rats. Following RT-PCR analysis, significant increase in mRNA levels of mGluR5, NR1, NR2A, and NR2B subunits of NMDA receptors was recorded in the amygdala of EW rats. EW had no significant effect on mRNA levels of PKC epsilon. MPEP (10 and 30mg/kg) significantly reduced the gene expression of mGluR5 and NR2A subunit. On the other hand, acute ethanol challenge significantly reduced the gene expression of mGluR5 and NR2B. Overall, the results show that MPEP (10mg/kg) significantly attenuated EW induced anxiety in the EPM and the OF through inhibition of mGluR5-PKC epsilon signalling pathway which attenuated the EW induced glutamatergic hyperexcitability in the amygdala by significantly reducing the abstinence induced increase in mGluR5 and NR2A gene expression.